The mediator role of hierarchical distance on social processes-HRM practices: An empirical analysis of Spanish firms - Triguero-Sánchez, Rafael (2016)
The literature pays little attention to non-linear models, especially regarding dimensions such as organizational culture. Therefore, the purpose of this paper is to test the role of hierarchical distance in the relationship between HRM practices and social processes. With a sample of 102 Spanish firms and using partial least squares structural equation modeling assessed this relationship. Results suggested mediation of hierarchical distance between HRM practices and social processes. Such results recommend that HR managers should consider hierarchical distance more carefully especially when creating HRM practices to improve relationships among employees. Thus, the politics of commitment function better when organizations are more horizontal and when tasks are commonly delegated, managers question employees frequently prior to making decisions, discussions are encouraged, and social relationships – both in and out of work – are valued, appear to provide the most benefit regarding competitive advantages generated through HRM practices.